Fatty Acid Metabolism in Symptomatic Patients with Mitral Valve Prolapse but without Coronary Artery Disease - Comparison with 201 Tl Myocardial Perfusion Scintigraphy - Voth, E.; Schicha, H.; Tebbei, U.; Neumann, P.; Emrich, D. (Nuklearmedizin - NuclearMedicine, 1987)
Using 123l-ω-heptadecanoic acid (HDA) and 201TI, respectively, myocardial fatty acid metabolism and perfusion were studied in 51 symptomatic patients with mitral valve prolapse (MVP) as diagnosed by ventriculography, and no evidence of coronary artery disease. Twelve subjects with normal coronary arteries and normal ventriculogram served as a control group for the evaluation of elimination kinetics of HDA. In the control group, the mean elimination halflife was 26.1 ± 3.6 min, whereas the patients with MVP had a mean value of ± 6.4 min. In patients with MVP, a high incidence concerning abnormalities of accumulation and/or elimination of HDA occurred, namely accumulation defects in 31 % and both prolonged and shortened elimination half-lives in 16% and 29%, respectively. Myocardial perfusion scintigraphy using 201TI showed abnormalities in 76%. Correlations were found between decreased uptake of HDA and prolonged elimination half-life as well as defects by 201TI, presumably due to ischemia based on small-vessel disease or abnormalities of cellular metabolism.Bei 51 symptomatischen Patienten mit Mitralklappenprolaps (MVP) und ausgeschlossener koronarer Herzkrankheit (KHK) wurden der Fettsäurestoffwechsel und die Perfusion des Myokards mittels 123J-ω-heptadekansäure (HDA) bzw. 201T1 untersucht. Zwölf koronarangiographierte Patienten ohne MVP und ohne KHK dienten als Kontrollgruppe bei der Untersuchung der Eliminationskinetik von HDA. In dieser Gruppe ergab sich eine mittlere Eliminationshalbwertszeit von 26,1 ± 3,6 min, bei den Patienten mit MVP ein Wert von 25,0 ± 6,4 min. Bei den Patienten mit MVP wurden häufig Störungen der Fettsäureakkumulation und/oder -elimination beobachtet; 31% hatten Myokardbezirke mit verminderter HDA-Akkumulation, 16% verlängerte und 29% verkürzte Eliminationshalbwertszeiten. Bei der 201T1 Myokardszintigraphie fanden sich pathologische Befunde in 76% der Patienten mit MVP. Eine verminderte Akkumulation von HDA zeigte signifikante Korrelationen zu einer verlängerten Eliminationshalbwertszeit und Defekten im 201T1 Szintigramm. Diese Beziehungen sprechen am ehesten für eine myokardiale Ischämie infolge einer “small-vessel disease” oder einer Störung des zellulären Metabolismus.